Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T20:35:58+01:00
3x do kwadratu +6= 3x(x-2)
3x do kwadratu +6=3x do kwadratu -6x / -3x do kwadratu
6=-6x /:-6
-1=x

(x + 2 ) (3 +x )=x(x+1 ) +2
3x+x do kwadratu +6+2x=x do kwadratu +x +2 /-x do kwadratu
5x + 6= x+2 /-x
4x +6 =2 /-6
4x=-4 / :4
x=-1
2009-12-03T20:37:10+01:00
A )3x do kwadratu +6= 3x(x-2)
3x² + 6 = 3x² -6x
3x² -3x² +6x = -6
6x = -6 /:(6)
x = -1

b) (x + 2 ) (3 +x )=x(x+1 ) +2
3x + x² + 6 +2x = x² +x +2
5x + x² +6 = x² +x +2
5x + x² - x² -x = 2 - 6
4 x = -4 /:4
x = -1
2009-12-03T20:38:42+01:00
(x+2)(3+x)=x(x+1)+2
3x+ x kwadrat+6+2x= x kwadrat+x+2
3x+2x-x=2-6
4x=-4 |:4
x=-1